Characteristics of femorotibial joint geometry in the trochlear dysplastic femur. Issue 3 (10th July 2014) - Frosch, Stephan; Brodkorb, Tobias; Schüttrumpf, Jan Philipp; Wachowski, Martin Michael; Walde, Tim Alexander; Stürmer, Klaus Michael; Balcarek, Peter
Abstract The medial and lateral tibia plateau geometry has been linked with the severity of trochlear dysplasia. The aim of the present study was to evaluate the tibial slope and the femoral posterior condylar offset in a cohort of consecutive subjects with a trochlear dysplastic femur to investigate whether the condylar offset correlates with, and thus potentially compensates for, tibial slope asymmetry. Magnetic resonance imaging was used to assess the severity of trochlear dysplasia as well as the tibial slope and posterior offset of the femoral condyles separately for the medial and lateral compartment of the knee joint in 98 subjects with a trochlear dysplastic femur and 88 control subjects. A significant positive correlation was found for the medial tibial slope and the medial posterior condylar offset in the study group (r2 = 0.1566; P < 0.001). This relationship was significant for all subtypes of trochlear dysplasia and was most pronounced in the severe trochlear dysplastic femur (Dejour type D) (r2 = 0.3734; P = 0.04). No correlation was found for the lateral condylar offset and the lateral tibial slope in the study group or for the condylar offset and the tibial slope on both sides in the control group. The positive correlation between the medial femoral condylar offset and the medial tibial slope, that is, a greater degree of the medial tibial slope indicated a larger offset of the medial femoral condyle, appears to represent a general anthropomorphic characteristic of distal femur geometry in patients with a trochlear dysplastic femur.